2013
DOI: 10.1097/wnr.0b013e328364b67c
|View full text |Cite
|
Sign up to set email alerts
|

Deviant neural processing of phonotactic probabilities in adults with dyslexia

Abstract: During language acquisition in the first year of life, children become sensitive to phonotactic probabilities such as the likelihood of speech sound occurrences in the ambient language. Because this sensitivity is acquired at an early age, the extent to which the neural system that underlies speech processing in adults is tuned to these phonological regularities can reflect difficulties in processing language-specific phonological regularities that can persist into adulthood. Here, we examined the neural proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
42
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(59 citation statements)
references
References 21 publications
(30 reference statements)
14
42
3
Order By: Relevance
“…high phonotactic probability and first syllable stress) are processed more efficiently, this should lead to easier change detection, indexed by greater MMN peak amplitudes and/or shorter latencies. This has been shown for phonotactic probability [36][37][38] . However previous studies investigating MMN sensitivity to syllable stress have been primarily conducted in languages with fixed-stress patterns [39][40][41][42] .…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…high phonotactic probability and first syllable stress) are processed more efficiently, this should lead to easier change detection, indexed by greater MMN peak amplitudes and/or shorter latencies. This has been shown for phonotactic probability [36][37][38] . However previous studies investigating MMN sensitivity to syllable stress have been primarily conducted in languages with fixed-stress patterns [39][40][41][42] .…”
mentioning
confidence: 59%
“…Oddball experiments in adults and children have demonstrated that the MMN component can be modulated by variations in phonotactic probability, i.e. the probability of the co-occurrence of phonemes in a language, where deviants with higher probability have been shown to elicit larger mismatch responses compared to deviants with low probability [36][37][38] . The paradigm has also been applied to study processing of syllable stress patterns in both real and pseudowords [39][40][41][42] .…”
mentioning
confidence: 99%
“…Finally, studies used an MMN paradigm (see Section 2 ) in which the phonotactic probabilities of stimuli are manipulated; that is, the sounds presented differed in their likelihood of occurrence in spoken language [ 130 , 131 ]. The MMN responses in this paradigm are expected to be stronger for stimuli with higher phonotactic probability [ 132 ].…”
Section: Associative Implicit Learning and Other Cognitive Procesmentioning
confidence: 99%
“…The MMN responses in this paradigm are expected to be stronger for stimuli with higher phonotactic probability [ 132 ]. Dyslexics showed less sensitivity than typical readers to such enhancement of MMN responses, which was interpreted to reflect a subtle deficit in auditory cortical tuning for phonemic regularities in natural speech [ 130 , 131 ]. Interestingly, some studies in typical readers suggested that lexical knowledge [ 133 ] and orthographic information [ 134 ] could influence perceptual learning of speech, referred to as phonetic recalibration.…”
Section: Associative Implicit Learning and Other Cognitive Procesmentioning
confidence: 99%
“…Phonotactic probability has also been implicated in memory for nonwords (Gathercole, Frankish, Pickering & Peaker, 1999; Messer, Leseman, Boom & Mayo, 2010), and in literacy-related skills , as in children learning to spell (Apel, Wolter & Masterson, 2006) and as evidenced by differences in processing stimuli that vary in phonotactic probability in children and adults with dyslexia (Bonte, Poelmans, & Blomert, 2007; Noordenbos et al, 2013). Finally, both electro- and magneto-physiological components have been identified for the processing of stimuli that vary in phonotactic probability (Hunter, 2013; Pylkkänen, Stringfellow, & Marantz, 2002).…”
mentioning
confidence: 99%